2019
DOI: 10.4103/tcmj.tcmj_136_18
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii and methicillin-resistant Staphylococcus aureus in long-term care facilities in eastern Taiwan

Abstract: Objective:The prevention of infections is crucial in long-term care programs. Investigations of the occurrence and sources of pathogens in long-term care facilities (LTCFs) are still lacking, especially in eastern Taiwan. In this study, we conducted a surveillance of two common pathogens, Acinetobacter baumannii (AB) and methicillin-resistant Staphylococcus aureus (MRSA), in LTCFs in Hualien.Materials and Methods:Pathogenic assays including isolation, identification, and antimicrobial susceptibility tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Based on the obtained findings, it can be stated that ERIC-PCR is a reliable method to demonstrate the clonal relatedness among A. baumannii recovered from different specimens of different patients. 36,37 The findings of this study are similar to the studies reported by Ying et al and Hammoudi et al who were able to cluster A. baumannii strains based on their genetic relatedness and confirmed cross contamination in the clinical settings. 51,53 Antimicrobial susceptibility tests were carried out on the obtained 51 MDR A. baumannii clinical isolates against a panel of antimicrobial agents composed of 14 different antimicrobial agents according to CLSI guidelines, 2018.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Based on the obtained findings, it can be stated that ERIC-PCR is a reliable method to demonstrate the clonal relatedness among A. baumannii recovered from different specimens of different patients. 36,37 The findings of this study are similar to the studies reported by Ying et al and Hammoudi et al who were able to cluster A. baumannii strains based on their genetic relatedness and confirmed cross contamination in the clinical settings. 51,53 Antimicrobial susceptibility tests were carried out on the obtained 51 MDR A. baumannii clinical isolates against a panel of antimicrobial agents composed of 14 different antimicrobial agents according to CLSI guidelines, 2018.…”
supporting
confidence: 91%
“…The Percentage of similarity among 51 isolates of A. baumannii was calculated using Jaccard's Coefficient. 37…”
Section: Antimicrobial Susceptibility Testing and Mdr Definitionmentioning
confidence: 99%
“…Analysis of ERIC-PCR dendrogram was constructed by the use of the UPGMA clustering method, Bionumeric program version 7.6 (Applied Maths). The Percentage of similarity among 34 strains of A. baumannii was calculated by the use of Jaccard's Coefficient [29].…”
Section: Molecular Typing Of Recovered Isolatesmentioning
confidence: 99%